2002
DOI: 10.3137/ao.400206
|View full text |Cite
|
Sign up to set email alerts
|

The water balance climatology of the Mackenzie basin with reference to the 1994/95 water year

Abstract: computed the mean annual basin temperature (T) to be -3.4°C, the mean annual basin precipitation (P) to be 421 mm and the mean annual basin evapotranspiration (E) to be 277 mm. A simple water balance was applied to test the consistency of the P and E fields with the observed basin discharge (Q). For the 24-year period 1972 to 1995, the mean annual residual (P-E-Q) for the water balance was -28.4 mm. This residual is a combination of errors in the three water balance components and the assumption of zero annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 30 publications
(31 reference statements)
5
42
1
Order By: Relevance
“…Geographically weighted regression (Ninyerola et al, 2000;Brunsdon et al, 2001;Marquínez et al, 2003) and a knowledge-based system (Nalder and Wein, 1998;Price et al, 2000;Daly et al, 2002), which combines multiple linear regression and distance weighting, have been used to estimate precipitation in areas where there are no stations nearby. Besides the traditional statistical and geospatial climatology commonly used in a geographic information system (GIS) (after Wilk and Andersson (2000)), a variety of geostatistical prediction techniques have been applied to climatic data (Phillips et al, 1992;Bacchi and Conati, 1996;Atkinson and Lloyd, 1998;Holawe and Dutter, 1999;Sousa and Santos Pereira, 1999;Todini and Pellegrini, 1999;Monestiez et al, 2001;Dalezios et al, 2002;Louie et al, 2002). Statistical, geostatistical and GIS integrated approaches have recently been outlined by Hartkamp et al (1999), Vajda and Venäläinen (2003) and Thomas and Herzfeld (2004), and Agnew and Palutikof (2000) used then for generating seasonal precipitation baseline climatologies at a high spatial resolution in the Mediterranean area.…”
Section: Introductionmentioning
confidence: 99%
“…Geographically weighted regression (Ninyerola et al, 2000;Brunsdon et al, 2001;Marquínez et al, 2003) and a knowledge-based system (Nalder and Wein, 1998;Price et al, 2000;Daly et al, 2002), which combines multiple linear regression and distance weighting, have been used to estimate precipitation in areas where there are no stations nearby. Besides the traditional statistical and geospatial climatology commonly used in a geographic information system (GIS) (after Wilk and Andersson (2000)), a variety of geostatistical prediction techniques have been applied to climatic data (Phillips et al, 1992;Bacchi and Conati, 1996;Atkinson and Lloyd, 1998;Holawe and Dutter, 1999;Sousa and Santos Pereira, 1999;Todini and Pellegrini, 1999;Monestiez et al, 2001;Dalezios et al, 2002;Louie et al, 2002). Statistical, geostatistical and GIS integrated approaches have recently been outlined by Hartkamp et al (1999), Vajda and Venäläinen (2003) and Thomas and Herzfeld (2004), and Agnew and Palutikof (2000) used then for generating seasonal precipitation baseline climatologies at a high spatial resolution in the Mediterranean area.…”
Section: Introductionmentioning
confidence: 99%
“…The grids provide better spatial coverage and can be easily combined or integrated with other geo-referenced environmental variables. For example, long-term series of climatological grids are used in studies of regional climate change and variability across Canada (Zhang et al, 2000); to build hydrological models that calculate water budgets (Hogg et al, 1996;Louie et al, 2002); to map plant-climate response in the context of forest planning and management (McKenney et al, 1996); to map plant hardiness zones for agriculture (McKenney et al, 2001); to assess aridity and the paleoclimatic context of recent droughts on the Canadian Plains (Sauchyn et al, 2002(Sauchyn et al, , 2003b; to verify the quality of dendroclimatology reconstruction (Watson, 2004), to evaluate the Canadian Regional Climate Model over the Mackenzie basin (MacKay et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Using NCEP data, Liu et al (2002) found that the vapour flux convergence (P-E) over the Mackenzie for WY 1995 was the lowest of the ten-year period 1987-96, associated with strong negative precipitation anomalies in spring and summer (Louie et al, 2002;Stewart et al, 2002). Another factor was the low efficiency at which vapour flux convergence was converted into discharge, in turn related to the pattern of summer precipitation recycling noted earlier, very warm summer conditions, and dry surface conditions that developed just prior to the water year (Stewart et al, 2002;Szeto, 2002).…”
Section: Results a P-e And Discharge For 1995-98mentioning
confidence: 99%